Numerical modelling of slope stabilization with xathan gum-treated soil - Tran Thi Phuong, An; Ilhan, Chang; Tran Thanh, Nhan; Gye-Chun, Cho (Vietnam Journal of Earth Sciences, 2022)
Biopolymer soil treatment has been introduced as the latest technological innovation in soil stabilization and improvement. Biopolymers with agar, guar, xanthan, casein, gellan and sodium alginate have been commonly studied to improve strength, reduce hydraulic conductivity and prevent erosion of highly permeable soil materials. Among those, xanthan gum is introduced to perform better in terms of lowering permeability. In this study, the effect of xanthan gum on slope stability under rainfall was evaluated via a 2D finite-difference program (FLAC) considering the wetting behavior of xanthan gum-treated soil. In order to obtain input parameters for numerical modelling, wetting soil-water characteristic tests, permeability tests, and direct shear tests were conducted on xanthan gum-treated soils. The numerical results support the application of biopolymers to soil erosion control during rainfall, mainly due to the significant decrease in the infiltration of xanthan gum-treated soil.